Religious Harmony Within Religious Manuscript (The Study of Serat Purwocampur) - Bisri Ruchani (Balai Penelitian dan Pengembangan Agama Semarang, 2013)
Javanese manuscript is a noble heritage that should be preserved. This study was conducted to determine the values of harmony contained in the Serat Purwocampur. The method used in this study on a content analysis and philology. Serat Purwocampur consists of four kinds of macapat song: Asmaradhana, Girisa, Pangkur, and Dhandhanggula. Briefly, this manuscript contains ancient stories and supernatural, such as gods associated with the prophets or otherwise. Value of harmony contained in this manuscript is the acculturation between Hinduism and Islam (Islamic Javanization). Islam spread peacefully in Java, in additions Islam also taught its followers (the Javanese) to perform religion both syari’at and hakikat.